Peningkatan Kapasitas Pengelola Kampung Edukasi di Desa Kembangkuning, Kabupaten Boyolali - Triyono, Agus; Rahmawati, Fitri Puji; Setiawan, Wisnu; Santoso, Budi; Yuwono, Iswahyudi Tejo (Universitas Muhammadiyah Surakarta, 2024)
In the development process in the era of globalization, empowerment is a very important form of development. The institutional partner in this service is Kembangkuning Village with Kampung Edukasi as the program implementation partner. The aim of this service is to improve the quality of service from partners who have been engaged in educational tourism. The implementation method is carried out in several stages, namely: situation analysis, program planning, implementation and evaluation. The results of the activities that have been carried out show that the potential for partner development is divided into two aspects, namely educational and industrial-based tourism. Partners have experienced an increase in quality in terms of understanding efforts to provide excellent service to every visitor. The digitization aspect is carried out through the development of a website and also barcodes for each collection in the museum.